2012
DOI: 10.1371/journal.pone.0037742
|View full text |Cite
|
Sign up to set email alerts
|

Adult Human Brain Neural Progenitor Cells (NPCs) and Fibroblast-Like Cells Have Similar Properties In Vitro but Only NPCs Differentiate into Neurons

Abstract: The ability to culture neural progenitor cells from the adult human brain has provided an exciting opportunity to develop and test potential therapies on adult human brain cells. To achieve a reliable and reproducible adult human neural progenitor cell (AhNPC) culture system for this purpose, this study fully characterized the cellular composition of the AhNPC cultures, as well as the possible changes to this in vitro system over prolonged culture periods. We isolated cells from the neurogenic subventricular z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 82 publications
0
51
0
Order By: Relevance
“…Two recent reports provided the first hints of the existence of pericytes in the human adult brain [13,14]; however, the groups reported different observations. Although Paul et al reported no coexpression of NSCs and pericyte markers by aBPMCs but rather an intrinsic neuroectodermal differentiation potential [14], Park et al reported coexpression of these markers but no neuroectodermal differentiation potential [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent reports provided the first hints of the existence of pericytes in the human adult brain [13,14]; however, the groups reported different observations. Although Paul et al reported no coexpression of NSCs and pericyte markers by aBPMCs but rather an intrinsic neuroectodermal differentiation potential [14], Park et al reported coexpression of these markers but no neuroectodermal differentiation potential [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, such perivascular MSCs, or "fibroblast-like cells," were also described in the adult human brain [13,14]. Both reports described fibroblast-like cells deriving from the perivascular niche as harboring long-term expandability and mesodermal differentiation potential [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited self-renewal capacity and the tendency toward acquisition of karyotypic aberrations are regarded as potential limitations of nonimmortalized NPCs for basic science and translational medicine studies [67,68]. In the present study, we used NPCs that had been immortalized by transduction with v-MYC [34].…”
Section: Discussionmentioning
confidence: 99%